Political Will Of Bogor City Government In Implementing Angkot Arrangement Policy During Bima Arya Sugiarto’s Two Leadership Periods (2016-2024) - Nursalim, Muhammad Iqbal; Ridwan, Ridwan (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
This study examines the Political Will of the Bogor City Government in implementing urban transportation policies, especially in structuring the operation of city transportation (angkot) during the two leadership periods of Mayor Bima Arya Sugiarto (2016-2024). This research departs from the still not optimal management of angkot, which contributes to congestion in Bogor City. This study aims to analyze the challenges in implementing reform programs, such as rerouting, vehicle age restrictions, integration with the BisKita Trans Pakuan system, and implementation of the Bogor Transportation Program (B-TOP). Policy implementation still faces several obstacles, including suboptimal supervision and the practice of illegal levies by specific individuals. The results show that Political Will faces challenges with coordination, supervision, and transparency. The Bogor City Government has made various efforts, including optimizing funding from the central government and establishing cooperation with the private sector to support the provision of infrastructure and strengthening transportation institutions. The success of transportation management requires collaboration between the government, business actors, and the community. Strong political will must be reflected in cross-sector synergies, consistent supervision, and transparent and sustainable governance.